Effect of Different Blood-Pressure-Lowering Regimens on the Blood Pressure Control among Hypertensive Patients Treated in Hospital Conditions - Anna Paczkowska; Karolina Hoffmann; Krzysztof Kus; Dorota Kopciuch; Tomasz Zaprutko; Piotr Ratajczak; Elżbieta Nowakowska; Wiesław Bryl (International Journal of Hypertension)
Background. Scientific references lack sufficient amount of data on analyses of the reasons for hospital admissions or assessment of efficacy of arterial hypertension treatment at hospitals. Objectives. The aim of the study was to evaluate the efficacy of antihypertensive drug therapy on the blood pressure control among hospitalized hypertensive patients. Methodology. A cross-sectional retrospective study consisted of 204 patients aged 18–65 years admitted to the hospital due to hypertension between January 2018 and December 2018. The study was based on analysis of electronic records, obtained from the medical database of the selected healthcare facility. Results. As a result of the treatment applied at the hospital, 65.19% of the patients achieved the desired degree of blood pressure normalization (≤130/80 mmHg). Vast majority of the patients during their stay at the ward would receive three or more hypertensive drugs (63.73%). The most frequently prescribed antihypertensive drug combinations included bitherapies such as diuretics + ACEI and ACEI + β-blockers and tritherapy such as diuretics + β-blockers and calcium channel antagonists and diuretics + ACEI and ARBs. The highest blood-pressure lowering effects were observed among patients receiving combination therapy of a ACEI, a diuretic, and a ARBs. Tritherapy induced a significant mean reduction of inpatients`s SBP compared with bitherapy (p=0.0001). Conclusion. During their hospital stay, vast majority of patients (65.19%) achieved normal values of blood pressure, mostly owing to combined treatment with several hypertensive drugs. Efficacy of the most frequently used combinations of hypertensive drugs in normalizing arterial pressure varies.